Organizational Systems, General Systems Approaches to Complex Organization - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1976)
This article reviews "Organizational Systems, General Systems Approaches to Complex Organization" by Frank Baker.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z